Revisiting The ASEAN-EU FTA Conundrums: Problems of Regional Actorness in Complex Negotiations - Andrew Malay Naufalibna Nasution; Pantri Muthriana Erza Killian (Universitas Cenderawasih, 2024)
This paper seeks to explain the role of regional actorness in complex negotiations by analyzing ASEAN and the EU’s attempt at creating a region-to-region free trade agreement. In 2007, ASEAN and EU initiated a region-to-region negotiation in the hope of creating one of the largest trading blocs in the world. However, until the end of 2023, or after 16 years of negotiation, not much progress can be observed. While there are several explanations for this, including the competing interest between major powers and the failure to manage diversity, this article argues that one core element for the slow progress is the differing levels of actorness—loosely defined as actors’ internal capability and external acceptance between ASEAN and the EU. The methodology used in this article is through a literature review. The literature itself consists of articles journals, books, websites, documents, and conference papers. Throughout the negotiation, ASEAN tends to display a lower degree of actorness, which leads to challenges in undertaking decisions and building a coherent front to external actors compared to the EU. Another crucial factor is the nature of the negotiation, which creates a multilayered problem for both actors. Thus, while there are several hindrances during the negotiations, the inherent difference in actorness between the two remains to be a challenge. KEYWORDS Actorness; Complex Negotiations Interregionalism; ASEAN; European Union